Potential Factors Associated with Pelvic Lymph Node Metastasis in Endometrioid Endometrial Carcinoma - Prakasit Karavanich; Atthapon Jaishuen (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To explore factors that associated with pelvic lymph node metastasis in endometrioid endometrial carcinomaMaterials and Methods: Two hundred and ninety-three patients with endometrioid endometrial carcinoma, who received surgical staging in Siriraj Hospital during 2008-2016, were studied. The relationship between pelvic lymph node metastasis and these data: demographic factors, biochemical markers, preoperative and intraoperative tumor characteristics were analysed by using a logistic regression model. Results: From multivariate analysis, associated factors were grade of tumor, platelet count, deep myometrial invasion (deep MI: more than half of myometrial invasion) and size of tumor. Platelet count and size of tumor were re-calculated. Thrombocytosis (platelet count more than or equal to 380,000/mm3) and large tumor (tumor size more than or equal to 6 centimeters) were statistically significant for cut-off point. Conclusion: Grade of tumor, platelet count, more than half of depth of myometrial invasion and size of tumor, were associated with pelvic lymph node metastasis in endometrioid endometrial carcinoma.